2003
DOI: 10.1155/s1110662x03000266
|View full text |Cite
|
Sign up to set email alerts
|

Titania aerogels: Preparation and photocatalytic tests

Abstract: Titania aerogels are suggested as promising photocatalysts [1]. In the present study aerogels were synthesised by sol-gel method combined with supercritical drying. Tetraisopropyl orthotitanate was used as a precursor, anhydrous methanol and isopropanol as solvents. Three aerogels were prepared using different ways of synthesis. Volumes and surface areas of micro- and mesopores of each aerogel were determined. XRD and SEM analyses were carried out. For comparison analyses were also performed forTiO2P25 Degussa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Titania aerogels are very interesting nano/microstructures, due to their low density, porosity, high pore volume, and large specific surface area [160][161][162][163]. Although they are commonly composed of NPs of titania, the resultant aerogel structure is much larger, and thus titania aerogels might be classified as 3D structures.…”
Section: Titania Aerogelsmentioning
confidence: 99%
“…Titania aerogels are very interesting nano/microstructures, due to their low density, porosity, high pore volume, and large specific surface area [160][161][162][163]. Although they are commonly composed of NPs of titania, the resultant aerogel structure is much larger, and thus titania aerogels might be classified as 3D structures.…”
Section: Titania Aerogelsmentioning
confidence: 99%
“…10 Ismail et al posited that networked, mesoporous TiO 2 modified with gold (Au) nanoparticles strongly enhanced UV-photocatalytic oxidation of methanol because electrons traveled over multiple nanoparticle lengths to reach the Au nanoparticles. 11 In these and other examples of photocatalysis at networked nanostructured titania, 12,13,14,15,16,17,18,19 the fundamental effects of electron (and hole) lifetime as well as electron mobility on photocatalytic activity remain open. In order to exploit the promise of a wired photocatalytic system, the dynamics of the charge carriers in the semiconductor network must be more rigorously understood.…”
mentioning
confidence: 99%
“…The supercrititical drying technique offers the possibility to vary the drying temperature and, hence, to tailor the specifications of the dried material. [57] In comparison with other media used in the supercritical drying procedure like acetone [58] or alcohols, [59,60,62] CO 2 is beneficial owing to its relatively mild supercritical conditions, especially the low supercritical temperature of 304.13 K. Recent investigations showed that supercritical drying leads to better results than, for instance, freeze-drying. CO 2 can be recycled easily; it is also non-flammable, non-toxic, and inexpensive.…”
Section: Synthesis Of the Aerogelsmentioning
confidence: 99%